Immune Response of White Shrimp (Litopenaeus vannamei) to Different Density and IMNV Challenge - Nur Komariah Baladrat; Moch Nurhudah; Heny Budi Utari (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchWhite shrimp (Litopenaeus vannamei) challenged with IMNV and different stocking densitiesThe water quality parameter values are getting worse along with the increase in stocking densityWhite shrimp THC value decreased with increasing stocking density and IMNV challenge testThe development of the IMNV increased with an increase in stocking density seen from the speed and percentage of the appearance of the clinical symptoms and histopathology results AbstractIncreasing in stocking density of shrimp affects the physiology and behaviour of their moving space. The health condition of shrimp is influenced by feeding, growth, and its susceptibility on disease. The aim of this study was to determine the development of immune response in relation to density and the presence of IMNV infection. This study used a completely randomized design (CRD) at density of 100 shrimp.m-2, 200 shrimp.m-2, and 400 shrimp.m-2, with three replications in each treatment. The shrimp used was 5,02±0,26 g and the virus infection was exposed orally. This research was facilitated at the Disease Research Centre Laboratory of Central Proteina Prima Company, Pasar Kemis, Tangerang for 30 days. The results showed that the Total Hemocyte Count (THC) in hemolymph of shrimp had different values between negative controls and challenged IMNV. The lowest THC value was found at a density of 400 shrimp m-2 (3.00x106ml-1). While the highest THC value was at a density of 100 shrimp.m-2 (4.75x106ml-1). This result is supported by the increasing value of water quality parameters along with the increasing density of shrimp. Histopathology changes on skeletal muscle and lymphoid organs confirmed that the development of IMNV infection was faster at high shrimp densities.